Analisis Kualitas Pelayanan Kartu Keluarga Pada Kelurahan Timbang Deli Kecamatan Medan Amplas Kota Medan - Vivi Andriani; Yusniar Lubis; Syafruddin Ritonga (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this article is to analyze the quality of family card services in the weighing deli sub-district, Medan Amplas sub-district, Medan City, bearing in mind the role of the kelurahan as one of the government agencies tasked with administering public services. in the implementation of Family Card services there are several problems that have not been resolved so that the service does not run well. The slow process of managing correspondence, employees not mastering technology and the minimum number of employees so that the Family Card service becomes ineffective. This is influenced by any factors in improving the quality of Family Card services in Timbang Deli Village, Medan Amplas District, Medan City. The research approach was carried out qualitatively by using data collection methods, interviews, observation and documentation and analyzed qualitatively. The results of this study indicate that the implementation of the Family Card service in Timbang Deli Village, Medan Amplas District, Medan City has been going quite well, but there are still a number of things that still need to be improved. The inhibiting factors for this public service are: inadequate resources, inadequate financial resources and inadequate infrastructure and lack of employee commitment.